Radiotherapy in pancreatic cancer. - Klautke, G; Brunner, T (2008)
UNLABELLED: PURPOSE AND APPROACH: To summarize the current knowledge on the role of radiotherapy in the treatment of pancreatic ductal adenocarcinoma (PDAC). The results of meta-analyses, phase III-studies, and phase II-studies using chemoradiation (CRT) and chemotherapy for resectable and non-resectable PDAC are reviewed. RESULTS AND CONCLUSION: The role of CRT is undefined in the adjuvant setting but there may be a role as additive treatment after R1 resection. Locally advanced borderline resectable tumors may shrink down and be subject to potentially curative resections. In locally advanced clearly unresectable cancers the effect of CRT as well as chemotherapy is poorly defined and the sequence of chemotherapy and CRT should be re-evaluated. Patients with PDAC should always be treated within studies to identify optimal treatment results.